Contemporary theatre Samuel Beckett : Waiting for Godot - Schneider, Alan.; Kuney, Jack.; Worthington, Miner; Films for the Humanities (Firm). (Princeton, N.J. Films for the Humanities, 1976)
A play that epitomizes both the modern condition and contemporary theatre. Presents Act II in its entirely, beginning with the return of Didi and Gogo to what they were doing in Act I - Waiting for Godot
VHS.
Narrator, Milo O'Shea.
Zero Mostel as Estragon, Bergess Meredith as Vladimir, Kurt Kasznaias Pozzo, Alvin Epstein as Lucky, Luke Halpin as the boy.
Keywords: Beckett, Samuel, 1906- -- Comedies